Beyond the trend; understanding perceived qualities of apartments over decades and design suggestion on future developments - Steffensen , Kajsa (My University, 2023)
Over the last centuries the way apartments are designed has changed along with the rest of society. While some effects of this are easily measured, like square meters and production costs, research has shown that certain values are much harder to quantify. A look into these immeasurable values highlights things like daylight, openness, materials, details, flexibility, and movement, etc. Previous studies have been made that explores the extent on which architects focus on these values while designing apartments today. Looking at the span over the eras is not as common. Through conversation with residents in apartments built over the course of the last 140 years, this thesis aims to shed light on the subjective preferences of the intended customer of the architect, which is always the person using the designed space. Interviews have been made in the homes of people with no architectural background, to see how they describe their apartments based on questions about these features. Here the discussion has been centred around these immeasurable values, and finding out whether the change in style over the years has made any difference in the advantages from these values. As one might guess, the different styles and fashions over the years have made a change in how many of these values are focused on, as well as advancements in technology has changed the necessity of some features. Overall, however, it seems as if the preferences of residents remain rather unchanged when it does come down to these specifics. They do not always focus on the presented values, but often they do. Daylight is something all interviewees mentioned as important, but reaching a room from several access points is only talked about if brought up as a topic. A resulting design suggestion has been made based on the appreciated historical features, and on the lived reality of everyday people that use these homes without any professional knowledge in the field of architecture.